Rancang Bangun Sistem Informasi Pengelolaan Stok Barang Berbasis Web pada PT. Perfekta Nusa - Faishal Maulana; Farizi Ilham; Agnes Laurencia (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Inventory management is an important aspect of company operations as it plays a role in maintaining product availability and supporting business processes. PT. Perfekta Nusa still faces several challenges in inventory management, such as unintegrated recording processes, delays in data updates, and the potential for errors in inventory input and reporting. This study aims to design and develop a web-based Inventory Management Information System at PT. Perfekta Nusa using the Waterfall system development method. The stages carried out include requirements analysis, system design, implementation, testing, and maintenance. The system was developed using web-based technology with MySQL database support. The main features developed include user authentication, product data management, incoming and outgoing goods transactions, inventory monitoring, and report generation. System testing was conducted using the Black Box Testing method and showed that all system functions operated according to requirements. The results indicate that the developed system can improve inventory management effectiveness, minimize recording errors, and accelerate data processing and information presentation.